Faster intervals, faster recoveries - intensified short VO2max running intervals are inferior to traditional long intervals in terms of time spent above 90% VO2max - Fleckenstein, D.; Braunstein, H.; Walter, N. (Frontiers in Sports and Active Living, 2025)
Introduction: High intensity interval training for improving maximal oxygen consumption (VO2max) is a fundamental component of specific preparation phases for middle- and long-distance runners. In this context, short intervals are very popular in practice. The aim of the present study was to determine whether increasing the intensity of short intervals around maximal aerobic speed (vVO2max), compared to traditional long interval runs, leads to a greater time spent above 90% VO2max.